Ekonomi Dan Penguasa (Pemikiran Ibn Taimiyah tentang Mekanisme Pasar) - Syarial Dedi (AL-FALAH : Journal of Islamic Economics, 2018)
The classical scholars not only focus on the issue of ritual worship, but also pay attention to the economic problems of society and even indicated theories of modern conventional economics is the adoption of the results of their thinking. One of them is Ibn Taymiyyah. Its has inspired the market mechanism. Prices are handed over to businesses naturally, without being interfered with by the government. On the other hand religion gives authority to the government that must be obeyed by the ruler in taking care of them. This study uses the method of literature with the conclusion that in the free market, the price is considered by the strength of supply and demand. Free market runs fair, reasonable, likes the same likes and no distortion. However, the market mechanism is not always running perfectly, often distortion occurs. In this condition, the state's role as the supervisor of development morality is needed to make people aware that moral norms and ethical values are very important as the principle of development that must be implemented in the life of the economy. This means that Ibn Taymiyya'hs economic thought is in line with the duties and authorities of the ruler.